(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Different sorts of urgent crises are treated with out-of-hospital acute medical treatment byemergency medical services (EMS). In addition to a large number of other employees that operate in thepre-hospital environment, the EMS team comprises paramedics. Pre-on-scene hospital’s decisionmakingis a significant component in the management of life-threatening conditions and the reduction ofmorbidity and death. Pre-hospital decision-making is a difficult process, thus it is important to recognizeit. This research was done to examine the decision-making process used by Saudi Arabia’s emergencymedical technicians.